The Study of Learning Motivation Analysis during COVID-19 Online Learning and Post COVID-19 Offline Learning - Langgar, Dorcas; Bani, Marsi; Ly, Petrus (International Journal of Social Service and Research, 2023)
This research is motivated by changes in the learning process due to the Covid-19 pandemic where the learning process during the Covid-19 pandemic uses online learning and post-covid-19 learning again uses the face-to-face (offline) learning process, where these two learning processes affect student learning motivation. The purpose of this study is to find out the picture of learning motivation during online learning, offline learning and comparing student learning motivation during online learning and offline learning. This research was conducted on students of Citra Bangsa Kupang Junior High School using a causal-comparative type of research. This research is an ex post facto type of research, which is research on data collected after a fact or event occurs. The population in this study were students of class VIII of SMP Citra Bangsa Kupang. The data sources used in this study are pimer data and secondary data, with data collection techniques using learning motivation questionnaire sheets. After getting all the data, the next step is to draw conclusions from this study by analyzing the data. The technique used to analyze this research is descriptive quantitative. The results of the research obtained are that student learning motivation during online learning during the Covid-19 pandemic is in the moderate category with an average score of 64. Student learning motivation during offline learning after the COVID-19 pandemic is in the high category with an average score of 82.4. There are differences in student learning motivation in participating in the online and offline learning process where student learning motivation during offline learning is higher than student learning motivation during online learning.